2014
DOI: 10.1038/mtna.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Mir-34: A New Weapon Against Cancer?

Abstract: The microRNA(miRNA)-34a is a key regulator of tumor suppression. It controls the expression of a plethora of target proteins involved in cell cycle, differentiation and apoptosis, and antagonizes processes that are necessary for basic cancer cell viability as well as cancer stemness, metastasis, and chemoresistance. In this review, we focus on the molecular mechanisms of miR-34a-mediated tumor suppression, giving emphasis on the main miR-34a targets, as well as on the principal regulators involved in the modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
374
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(397 citation statements)
references
References 151 publications
10
374
1
3
Order By: Relevance
“…Dysregulation and dysfunction of miRNAs leads to the initiation and development of cancers, indicating that miRNAs are important molecules that can potentially be used for the diagnosis and treatment of cancers (22). miRNA-34a has previously been identified to be frequently aberrantly expressed in human cancer, and involved in the regulation of cancer cells as a tumor suppressor (13). A previous Figure 2.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dysregulation and dysfunction of miRNAs leads to the initiation and development of cancers, indicating that miRNAs are important molecules that can potentially be used for the diagnosis and treatment of cancers (22). miRNA-34a has previously been identified to be frequently aberrantly expressed in human cancer, and involved in the regulation of cancer cells as a tumor suppressor (13). A previous Figure 2.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, miRNAs may serve as potential biomarkers and targets for the diagnosis and treatment of various types of cancer (12). miRNA-34a is an important regulator of tumor suppression, and acts by controlling cellular proliferation, cellular differentiation and the survival of cancer cells (13). A previous study demonstrated that the expression of miRNA-34a in GC was markedly downregulated, and that miRNA-34a was able to significantly inhibit epidermal growth factor receptor (EGFR)-signaling-dependent matrix metalloproteinase-7 (MMP-7) activation, which suggested that miRNA-34a may serve as a tumor suppresser to inhibit the cellular proliferation, migration and invasion of GC cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-34a can act as a tumor-suppressor by regulating processes such as the cell cycle differentiation, apoptosis, cancer cell viability, metastasis and chemoresistance. miR-34a might also have a benefit of a new therapeutic concept based on replacement of this miRNA expression and delivery of miRNA mimics through nanotechnology into cancer tissues without side effects on normal tissues [20].…”
Section: Regulation Of Mirna Expression and Its Epigenetic Silencingmentioning
confidence: 99%
“…Overall performance might be improved by combination of biomarkers within different molecular classes including cell-free DNA/ RNA, DNA methylation and many other [25]. Another described function of miRNAs is that they may act similar to hormones after being released from donor cells and are delivered from body fluids into receptor cells located in other areas [20]. However, a study analyzing circulating miRNAs from blood samples of healthy people argues against the hormone-like impact on target tissue, mainly due to extremely low concentration of circulating miRNAs when compared with plasma concentration of steroid hormones.…”
Section: Detection Of Cancer Biomarkers In Body Fluidsmentioning
confidence: 99%
“…103 Since then, several studies have demonstrated that miR-34 is an important regulator S53 of multiple oncogenes involved in cell cycle control, cell proliferation, apoptosis, and metastasis and, consistent with a function role in cancer, its expression is deregulated in many cancer cells. 116 These data suggested that miR-34 mimics might be an attractive therapeutic strategy to restore the normal regulation of a range of cell death and survival genes in cancer cells. Consistent with this hypothesis, the mir-34 mimic MRX34, a lipid-formulated miR-34 mimic, has demonstrated efficacy in several preclinical models of cancer.…”
Section: Clinical Experience With Mirna Modulatorsmentioning
confidence: 99%